Mutagenic activity of sweepings and pigments from a household-wax factory assayed with Salmonella typhimurium - Varella, S. D.; Pozetti, G. L.; Vilegas, Wagner [UNESP]; Varanda, Eliana Aparecida [UNESP] (Elsevier B.V., 2004)
The mutagenic activity of garbage originating from a household wax industry was determined by the Salmonella/microsome assay, using the bacterial strains TA100, TA98 and YG1024. The garbage was obtained by sweeping the floor of the factory at the end of the work shift. Organic compounds were extracted by ultrasound for 30 min in dichloromethane or 70% ethanol. After evaporation of solvent, these extracts (HFS: household-wax factory sweepings) were dissolved in DMSO, and were tested for the mutagenic activity at varying concentrations (HFS-ET: 0.08-0.68 mg/plate, HFS-DCM: 0.60-7.31 mg/plate). The colouring agents (pigments) used in the production of the wax were also dissolved in DMSO and tested with the assay. The concentrations tested for each pigment were: Amaranth: 0.46-3.65 mg/plate, Auramine: 0.15-1.2 mg/plate, Tartrazine: 0.46-3.65 mg/plate and Rhodamine B: 0.22-1.82 mg/plate. Both ET and DCM organic extracts had mutagenic activity, especially in the YG1024 strain. The pigments behaved in a similar way, demonstrating that YG1024 was the most sensitive strain for the detection of mutagenicity, and that metabolization increased the activity. Human exposure (occupational and non-occupational) to industrial residues generated during the household-wax manufacturing and packaging process should be monitored, since this type of garbage is normally deposited in the environment without any control. (C) 2004 Elsevier Ltd. All rights reserved.
Keywords: mutagenic activity; Salmonella typhimurium; industrial garbage mutagenicity; pigments